OPTIMALISASI PENGECATAN MENGGUNAKAN MODEL WATER TRANSFER PRINTING PADA LOGAM - Roni Suhartono; Susilawati Susilawati (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2020)
Painting the water transfer printing model on metal is the job of covering the surface of a metal object using water as the medium. The problem that often occurs is that the film does not want to stick on the surface to be painted. This is mostly due to things like the slope of an object, the condition of the water, and even the time needed. To solve these problems it is necessary to use a structured and patterned painting method. The research that has been done produces the right work steps to maximize the painting results using a water transfer printing model. The important point to do in painting using this model is the room that is not windy, the need for primers before painting, the slope of the water condition must be clean and calm and the temperature is around 32̊, the condition of the film is clean, the activation time of the film is about 60 seconds and the angle of the object when dipped 40-50̊. This important point makes painting using the water transfer printing model more optimal. Keywords: Metal, Optimization, Water Transfer Printing